TANGGUNG JAWAB HUKUM NOTARIS TERHADAP AKTA YANG DIBUATNYA SETELAH BERAKHIR MASA JABATANNYA DI TINJAU DARI PASAL 65 UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - Rico Andriansyah (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
Notary is defined asanauthorized public official to make authentic deed and other authorities referred to Acts or any other laws of Indonesia.The purpose of this study is to find out what sort of Notary responsibilities, SubstituteNotary, and Acting Notary on deeds made after the end of his term, and to find out the time limit of liability of Notary, Substituted Notary, and Acting Notary on each deed made or supervised by notaryreffered to Article No. 65 of Indonesian Notary Act (UUJN).This study used juridical normative method that studying laws in Indonesian Act.This study focused on documents or literature reviews related to theories, relevant opinion to the issues of the study.The results showed that Notary as an authorized public official (openbaarambtenaar) to make authentic deeds and to be responsible for his actions related to his profession.The scope of a Notary liabilityincludes: both civil liability and crime, based on UUJN and the ethics code of Notary. To determine the validity of liability from Notary, Substituted Notary, and Acting Notary for the deed made or supervised by, it must be reffered to the concept of the Notary as a Profession (ambt).The provisions concerning with the validity of liability shall be sued in the court for the parties aggrieved by the violation in authentic deed based on the provisions expiry.  Keywords: Responsibility, Notary, authentic deed, Ends of term.